BUSINESS MODEL CANVAS SEBAGAI MEDIA PENGGALIAN POTENSI DESA DAN PENILAIAN KELAYAKAN USAHA BUMDES - Sunaryono (Jurnal Ekonomi STIEP, 2020)
Villages in Indonesia generally have natural resources that can be one of the potentials that can be developed and can improve the economy of the village community. Lack of human resource capacity in the village makes these various natural resources cannot be managed properly. Because of this the village ministry has made a regulation that requires BUMDes in every village and may get initial funding from the Village Fund which is the transfer of funds from the center directly to the village. And with the presence of BUMDes, it is hoped that it can explore the potential of the village and help encourage economic growth in the village, and as a tool to explore the potential of the village is designed a media called the "Business canvas plan". With this media, it is not only the village potential that can be mapped but also can be used as a media to make a business analysis and assess the business feasibility of a BUMDes business unit. This business canvas plan is described in a paper divided into 9 boxes in the sequence according to Osterwalder as follows: customer segments, value propositions, customer relationships, channels, key resources, key activities, key partners, cost structures, revenue streams. This research uses Literature Research Methods and Community Based Research through In Depth Interview (IDI), and offline / online surveys. And with this research literature study will also carry out the process of collecting data by examining books, documents, journals, and other relevant sources. And from the literature obtained, it can be concluded that the Business canvas plan can be used as a media in exploring the potential of the village as well as a medium to assess the feasibility of BUMDes businesses in managing the village's potential.